2022
DOI: 10.1039/d2dt01060g
|View full text |Cite
|
Sign up to set email alerts
|

Water as a solvent: transition metal catalyzed dehydrogenation of alcohols going green

Abstract: The long-established practice of using organic solvents in synthetic chemistry is currently becoming a major focus for environmental alarms as many of the chemical wastes are generated in the form...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Therefore, great efforts were made to explore the possiblility of TM-catalyzed direct substitution of alcohols in aqueous media. [10] The seminal reports on palladium-catalyzed substitution of allylic esters in a two-phase aqueous-organic medium, suggested that the active π-allylic Pd species can be stale enough in water. [11] Afterwards, accompanied by the in-depth understanding of the stability and catalytic activity of TM active species in aqueous media, the alcohol-based Tsuji-Trost reaction in aqueous media developed rapidly in recent decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, great efforts were made to explore the possiblility of TM-catalyzed direct substitution of alcohols in aqueous media. [10] The seminal reports on palladium-catalyzed substitution of allylic esters in a two-phase aqueous-organic medium, suggested that the active π-allylic Pd species can be stale enough in water. [11] Afterwards, accompanied by the in-depth understanding of the stability and catalytic activity of TM active species in aqueous media, the alcohol-based Tsuji-Trost reaction in aqueous media developed rapidly in recent decade.…”
Section: Introductionmentioning
confidence: 99%
“…Development of an atom‐economical reaction in aqueous media is one of the most important goals of green organic synthesis. Therefore, great efforts were made to explore the possiblility of TM‐catalyzed direct substitution of alcohols in aqueous media [10] . The seminal reports on palladium‐catalyzed substitution of allylic esters in a two‐phase aqueous‐organic medium, suggested that the active π‐allylic Pd species can be stale enough in water [11] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been growing interest in the use of water as a solvent for catalytic reactions due to its abundance, low cost, and environmentally friendly properties. [11][12][13] In some cases, catalytic conversions are often better in an aqueous medium than in pure organic solvents due to the unique features of water such as high dielectric constant, the ability to act as a nucleophile or a leaving group, and the ability to solubilize polar reactants and catalysts. [14][15][16][17][18] Although homogeneous CuAAC can proceed in aqueous medium, the presence of an organic co-solvent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Late transition metal complexes of PNN and PNP type pincer ligands have proven widespread applications in synthesis, different types of bond activation, , and catalysis . Different types of PNN and PNP ligands used by various groups are shown in Figure .…”
Section: Introductionmentioning
confidence: 99%